Frecuencia de enterocolitis necrotizante en el neonato pretérmino según el peso al nacer hospital regional docente de trujillo: enero 2000 - enero 2015 - Villegas Vicente, Luis Angel (2017)
To determine the frequency of the newborn infant with a diagnosis of necrotizing enterocolitis according to birth weight. Method: Descriptive, retrospective - cross sectional study of 34 neonatal necrotizing enterocolitis neonates registered in the perinatal computer system of the Regional Teaching Hospital of Trujillo for 15 years. They were grouped a) according to gestational age in moderate to late neonates, very prétermines, extreme préterminos and b) according to the weight in low birth weight, very low weight and extreme low weight. Results: It was found that the frequency of the neonate infant with diagnosis of necrotising enterocolitis was a) according to the gestational age: neonates moderate to late 44% (15/34), neonate very préterminos 32% (11/34) and end-to-end préterminos 24 % (8/34) b) according to weight: with low birth weight 44% (15/34), with very low birth weight 27% (9/34) and with extreme low birth weight 29% (10/34). Conclusions: The highest frequency of necrotizing enterocolitis was found in the group of moderate to late men with low birth weight, while the group of extreme and very low birth weight had the lowest frequency